INTENSI MEMBELI KOSMETIKA PEMUTIH KULIT DITINJAU DARI KELENGKAPAN INFORMASI PRODUK PADA LABEL KEMASAN - Siwi, Ari Aria Catur; Meiyanto, Sito (Faculty of Psychology, Universitas Gadjah Mada, 2002)
The purpose of this study was to examine the effect of completeness of product knowledge on purchasing intention of skin whitening cosmetics. The subjects were 120 women who Senior High School graduatees at least. They were assigned randomly and the controlled group consisted of 60 women. The experimental group was given an skin whitening cosmetics consisted of completed product knowledge of label, but the controlled group was given an incompleted one. Both group were examined the intensity of purcahasing intention of skin whitening cosmetics. Data of this research were collected through purchasing intention questionnaire. Data were analyzed by t-test and the result showed that there was a significant differences between the experimental group and the controlled group with t= 3,431, p=0,001. Based on the result, it could be concluded that the completeness level of product knowledge was effective to increase purchasing intention of skin whitening cosmetics. Keywords: purchasing intention, product knowledge on label of package.